Ответы и объяснения

2012-12-25T13:32:23+04:00

513\(23+Х)+513/(23-Х)=46 (домножим обе части на (23+Х)(23-Х)

513(23-Х)+513(23+Х)=46(529-Х²)

11799-513Х+11799+513Х=24334-46Х²

23598-24334=-46Х²

-736=-46Х²

Х²=-736: (-46)

Х²=16

Х=√16

Х=4.

Ответ: Х=4.

Лучший Ответ!
2012-12-25T13:33:24+04:00

513\(23+Х)+513/(23-Х)=46; общий знаменатель - (23 + х)(23 - х) умножаем на него обе части

513(23-Х) + 513(23+х) = 46(23 + х)(23 - х);

11799 - 513x + 11799 + 513x = 24334 - 46x^2;

46x^2 = 736;

x^2 = 16;

x = 4;